Application of Lactobacillus inoculant from various rice paddy (Oryza sativa) to total mixed ration silage microbial composition (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Wahyudi A, Hendraningsih L, Sutawi S, Siskawardani DD. 2022. Application of Lactobacillus inoculant from various rice paddy (Oryza sativa) to total mixed ration silage microbial composition. Biodiversitas 23: xxxx. Evaluation of microorganisms profile of total mixed ration (TMR) silage inoculated with lactic acid bacteria (LAB) from local rice paddy (Oryza sativa L.) in tropical climate was analyzed to solve the feed management system. This study aimed to compare the effect of local LAB inoculants with commercial strain Lactobacillus plantarum FCC 123 on microorganisms composition of TMR silage in small-scale silage preparation. LAB was isolated from whole crop rice (w) and rice straw (s). Local rice paddy was planted in field around the University of Muhammadiyah Malang, East Java Province, Indonesia. Four rice paddy varieties: Membramo (M), Ciherang (C), Rajalele (R), and Impari (I) were utilized for isolation of LAB. Then, LAB was selected and purified in lactobacilli deMan Rogosa sharp agar (MRSA) and partially stored in dimethyl sulfoxide (DMSO) at -30°C as microbial stock. These selected LAB was used as inoculants at room temperature for 30 days TMR silage incubation. Completely randomized design (CRD) with 6 treatments (T0: TMR without fermentation, T1: TMR silage without inoculants, T2: TMR silage with L. plantarum FCC 123, T3: TMR with Local LAB Cs, T4: TMR silage with local LAB Mw, T5: TMR silage with local LAB Rs) were applied. Microorganism composition of LAB, aerobic bacteria, coliforms, clostridia, and mold was measured as experiment parameters. This research showed that LAB could be isolated and identified from all local paddy rice, both whole crop and straw. The implementation of local LAB on ensilage TMR was not significantly different from commercial L. plantarum FCC 123. Both local and commercial strains increased LAB population and suppressed harmful microbes (coliform, aerobic bacteria, and mold). The LAB isolates from local paddy rice could well act as an inoculant for TMR silage preparation in tropical climate.
Keywords: Ciherang, Clostridia, Coliform, lactic acid bacteria, microorganism, mold, TMR silage